Pediatric CKD: Integration of Magnetic Resonance Spectroscopy and Volumetric Analysis - Manal Farouk Eltohamy, Mohamed Ibrahim Amin , Maha Ibrahim Metwally , Alaa Ramadan Mohamed Elsaid Eissa, Mona Hamed Gehad, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Pediatric chronic kidney disease (CKD) is increasingly recognized as a systemic disorder withprofound neurological consequences. Even in early stages, CKD can impair neurodevelopment throughmechanisms including chronic uremia